2013
DOI: 10.1371/journal.pone.0063925
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Functional Annotation of Seventy-One Breast Cancer Risk Loci

Abstract: Breast Cancer (BCa) genome-wide association studies revealed allelic frequency differences between cases and controls at index single nucleotide polymorphisms (SNPs). To date, 71 loci have thus been identified and replicated. More than 320,000 SNPs at these loci define BCa risk due to linkage disequilibrium (LD). We propose that BCa risk resides in a subgroup of SNPs that functionally affects breast biology. Such a shortlist will aid in framing hypotheses to prioritize a manageable number of likely disease-cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 94 publications
(168 reference statements)
0
46
0
Order By: Relevance
“…The potentially functional implications of rs6828523 or SNPs highly correlated with rs6828523 (r 2 >0.6) are unclear as they are not located within any strong regulatory elements (Supplementary Figure 3). Also, a more comprehensive investigation of the functional effects of the 41 SNPs associated with overall breast cancer risk did not identify a SNP in LD with rs6828523 coinciding with a regulatory genomic feature 30 . ADAM29 encodes a disintegrin-metalloproteinase.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The potentially functional implications of rs6828523 or SNPs highly correlated with rs6828523 (r 2 >0.6) are unclear as they are not located within any strong regulatory elements (Supplementary Figure 3). Also, a more comprehensive investigation of the functional effects of the 41 SNPs associated with overall breast cancer risk did not identify a SNP in LD with rs6828523 coinciding with a regulatory genomic feature 30 . ADAM29 encodes a disintegrin-metalloproteinase.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, ELL has been found to be essential for the transcription of rapidly induced genes, and therefore plays a key role in quick responses to environmental changes 34 . Rhie et al identified another SNP (rs2303696) in LD with rs4808801 (r 2 = 0.79) located in the promoter region of ISYNA1, and likely to affect ISYNA1 expression 30 . ISYNA1 encodes an inositol-3-phosphate synthase enzyme that catalyses the synthesis of inositol 1-phosphate from glucose 6-phosphate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one SNVs were selected (Supplementary Table S1): 11 from O'Brien et al, 9 rs889312, an expression quantitative trait locus (eQTL) SNV, 10,11 and three further SNVs in high linkage disequilibrium (LD) with the former all located at 5q11.2 (Supplementary Table S2), as well as seven further SNVs were selected from Rhie et al 12 We preferred SNVs associated with oestrogen receptor α-positive (ER+) BC risk (often higher than for all BC) and close to coding sequences, to maximise the use of genotyped data without imputations of allelic variant status.…”
Section: Methodsmentioning
confidence: 99%